Manajemen Perencanaan Sumber Daya Manusia Di Bidang Pendidikan - Muqopie, Abdullah; Zohriah, Anis (Jambura Journal of Educational Management, 2024)
Human Resource Management (HRM) planning in the educational context is an integral part of efforts to achieve quality educational development goals. Educational human resource planning involves identifying human resource needs, assessing availability, and developing strategies to ensure that teachers, support staff, and administrators have the necessary qualifications, skills, and support. This article is included in the qualitative research method with an approach, namely library research. In the literature study, through efficient and sustainable educational HR management planning, we can improve the quality of education, achieve better educational development goals, and prepare competent and educated human resources for the future.